ETHNOSCIENCE-BASED E-FLIPBOOK FOR ENHANCING SCIENCE LITERACY IN ELEMENTARY SCHOOL: A LITERATURE REVIEW - Saiyida Alifia Rachmad; Suryanti; Farida Istianah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Science literacy remains a critical competency for elementary school students in the 21st century, yet its development continues to face significant challenges in Indonesian educational contexts. This literature review examines the theoretical foundations and empirical evidence supporting the development of an ethnoscience-based electronic flipbook (e-flipbook) to enhance science literacy among Grade 4 elementary school students. The review systematically analyzes relevant literature on four interconnected themes: science literacy in elementary education, ethnoscience as a culturally responsive approach in science learning, e-flipbook as an interactive digital learning medium, and the integration of local wisdom into primary school science curricula. Findings reveal that ethnoscience-based learning effectively bridges indigenous cultural knowledge with formal scientific concepts, making abstract science content more contextual and meaningful for students. Furthermore, the integration of digital interactive media such as e-flipbooks has consistently demonstrated improvements in student engagement, motivation, and conceptual understanding across multiple studies. The Kampung Kue Rungkut context in Surabaya presents a rich ethnoscience source, particularly regarding the concept of matter state changes embedded in traditional cake-making practices. This review concludes that the development of an e-flipbook grounded in the ethnoscience context of Kampung Kue Rungkut holds strong potential as an innovative and effective instructional medium for building science literacy competencies among Grade 4 students. Implications for curriculum development and future research directions are discussed.